ChatGPT in Supply Chains: Initial Evidence of Applications and Potential Research Agenda - Guilherme Francisco Frederico (Logistics, 2023)
Background: ChatGPT has been largely discussed since it was launched in November 2022. Problem statement: the main approaches of ChatGPT in the recent and scarce literature are more focused on the impacts for general use, applied sciences and educational systems, which evidences a relevant gap for the management field, especially related to the supply chain area. Objectives: as a novel and initial contribution, this article aims to provide a viewpoint with the main applications and other issues regarding ChatGPT in supply chains, based on the initial discovered evidence. Methods: This viewpoint article is grounded on the few articles available in specialized magazines, blogs and company websites that approach potential applications and other issues of ChatGPT in supply chains, as a systematic literature review was not possible due to the absence of papers approaching the subject in the research databases. Contributions: this article contributes to the practitioners involved in supply chain activities who desire to have an initial and structured content related to the impacts and applications of ChatGPT on supply chains. It also seeks to encourage researchers on further research deployments in this field by presenting potential research agenda topics. Results: first evidence based on quality results from the analyzed content showed that, although it may take time until this technology evolves to a desirable level of maturity, it may be applied in different areas of supply chain management (e.g., route optimization, predictive maintenance, order shipment, customer and supplier relationships, data analysis, ordering process, automating invoices, reducing waste, workforce training and guidance, amongst others), with a potential generation of significant benefits such as cost reductions and the improvement of supply chain performance.